Value-based Education in Culture and Curriculum. Gandhi’s Ideas for Sustainable Development - Moganty , Varalakshmi (2017)
Sustainable development has an imperative value. It is not associated with a mere raise in the purchasing capacity. Human values help sustenance of life lived in quality terms. These are the values people respected and observed from generations by historical persons, families, and nations. Values like dharma(justice), satya (truth), karuna (kindness), dana (charity), samapatti (sharing of one’s prosperity), dhairya (bravery), swatantra (liberty), and swarajya (self-rule) are some eternal human values which really help people’s lives and sustenance of human societies. History evinced how certain people adhered to these values and saved nations from hunger and slavery. Mother Theresa, Mahatma Gandhi, Abraham Lincoln, Martin Luther King, and Nelson Mandela not simply remained in history but inspire even today. Yet, we live in a world of economic development departing ourselves to value-linked culture. Children are also being taught and brought up in this world of corporate education and consumerism, so they will suffer tomorrow with the way we up bring them. Gandhi’s idea of education rather helps the child and youth grow healthy and confidently. But Gandhi’s Nai Talim or new education is actually preceded by Gandhi’s insights on self-reliant youth, self-sufficient villages, respect for nature in view of the adverse effects of undue industrialization, urbanization, unemployment and moral decay of societies. Hence this paper attempts to show the intricate relation of child’ education with Gandhi’s moral precepts, protection of village life and environment to provide sustainable development.